Analisis faktor-faktor yang mempengaruhi produksi kopi Arabika di Desa Kuta Rayat, Kabupaten Karo - Muhammad, Fadhil; Hernosa, Siswa Panjang (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
This research aimed to analyze and determine how much effect the factors of capital, land area, labor and fertilizer used have on Arabica coffee production in Kuta Rayat Village, Naman Teran District, Karo Regency. This research was conducted by interviewing and filling out questionnaires with 35 samples of Arabica coffee farmers. The method used in this research was quantitative methods and multiple linear regression analysis. Based on the results of the linear regression test in this study, it showed that the Capital variable (X1), the Land Area variable (X2), the Fertilizer variable (X4) have a positive and real effect on increasing Arabica coffee production, while the Labor variable (X3) has a significant effect. negative impact on Arabica coffee production. Based on the results of the T – test, the sequence of variables that is most significant in increasing Arabica coffee production is the Fertilizer variable (X4), the Land Area variable (X2), the Capital variable (X1), and the Labor variable (X3).